The investigation of a non-transition metal fluoride as a cathode material for lithium batteries - Owen, Nathan (Cranfield University, 2012)
Lithium ion batteries are fast becoming the consumer choice for powering their electronic devices. However, current lithium batteries energy densities are not suf- ﬁciently high, and cost per kWh suﬃciently low, to be widely accepted as batteries in electric vehicles. In order to reduce the cost and increase the energy density it may be necessary to move away from intercalation electrode materials, that are limited by the number of vacant lithium interstitial sites available, to conversion reaction materials that can allow multiple electron transfer. This thesis looks to investigate the use of a non- transition metal ﬂuoride as a cathode material in a primary or secondary lithium battery. Initial results for the ball milled material show speciﬁc energy densities over 2050 Wh/kg. The initial energy density rapidly faded over a period of a few cycles due to the structural change of the material and unwanted reactions with the electrolyte. These were identiﬁed by investigating the mechanism of the one stage discharge and charge proﬁle. To further improve the cycling results nanorods were synthesised which improved the rate capability to provide an energy density of over 1250 Wh/kg at a discharge rate of 0.25C. The capacity over repeated cycling was also improved but the same problems that plagued the ball milled samples were also apparent in the nanorod samples. It was found during the initial investigation of the non-transition metal ﬂuoride material that it is rechargeable, but for a limited number of cycles partly due to its poor kinetics. It has the potential to be a good rechargeable battery material but if not can satisfactorily compete with commercial primary batteries in terms of energy density and cost, as it is a very cheap material.